Harvesting energy from vibrations of the underlying structure - Han, Bo; Spyridon, Vassilaras; Papadias, Constantinos B.; Soman, Rohan N.; Kyriakides, Marios; Onoufriou, Toula; Nielsen, Rasmus Hjorth; Prasad, Ramjee Venkatesha (My University, 2013)
The use of wireless sensors for structural health monitoring offers several advantages such as small size, easy installation and minimal intervention on existing structures. However the most significant concern about such wireless sensors is the lifetime of the system, which depends heavily on the type of power supply. No matter how energy efficient the operation of a battery operated sensor is, the energy of the battery will be exhausted at some point. In order to achieve a virtually unlimited lifetime, the sensor node should be able to recharge its battery in an easy way. Energy harvesting emerges as a technique that can harvest energy from the surrounding environment. Among all possible energy harvesting solutions, kinetic energy harvesting seems to be the most convenient, especially for sensors placed on structures that experience regular vibrations. Such micro-vibrations can be harmful to the long-term structural health of a building or bridge, but at the same time they can be exploited as a power source to power the wireless sensors that are monitoring this structural health. This paper presents a new energy harvesting method based on a vibration driven electromagnetic harvester. By using an improved Maximum Power Point Tracking technique on the conversion circuit, the proposed method is shown to maximize the conversion coefficient from kinetic energy to applicable electrical energy. Reprints and permissions: sagepub.co.uk/journalsPermissions.nav.
Keywords: Energy harvesting; Maximum power point tracking; Micro generator; Structural health monitoring